Carbon nitride quantum dots (CNQDs)/TiO2 nanoparticle heterojunction photocatalysts for enhanced ultraviolet-visible-light-driven bisphenol a degradation and H2 production. (3rd September 2020) - Guo, Ruobin; Zeng, Dedong; Xie, Yu; Ling, Yun; Zhou, Dan; Jiang, Liushan; Jiao, Wenyu; Zhao, Jinsheng; Li, Shiqian
Abstract: The extension of the absorption band of solar energy is an efficient strategy to dramatically enhance the application value of TiO2 . Based on this, we have prepared carbon nitride quantum dots (CNQDs)/TiO2 nanoparticle heterojunctions by mixing TiO2 and the as-prepared CNQDs by the simple mechanical stirring method. The synthesized CNQDs-x/TiO2 composites were systematically characterized in term of their physicochemical properties, the performance of photocatalytic degradation of Bisphenol A, and their photocatalytic hydrogen evolution performance under stimulated sunlight. The CNQDs/TiO2 nanoparticle exhibited a lattice spacing of 0.352 nm, assigning to the (101) crystal plane of anatase phase TiO2. Intriguingly, the modification of TiO2 nanoparticle with CNQDs can indeed get a narrower optical band gap of 3.02 eV, with a wider absorption range extending to visible light region and could enhance their overall photocatalytic performance over the commercially TiO2 nanoparticles. In Addition, it was demonstrated that the ratios of CNQDs to TiO2 exhibited obvious influence on the photocatalytic performance of the obtained composite catalysts. By contrast to the pure TiO2, all the CNQDs-x/TiO2 composites displayed higher photocatalytic activities, and the CNQDs-2/TiO2 possessed the highest photocatalytic degradation capacity towards bisphenol A with a reaction rate constant 0.30 (0.17 for pure TiO2 ). Meanwhile, the H2 production rate of CNQDs-2/TiO2 sample is about 30 μmol g −1  h −1 higher than that of the pure TiO2 nanoparticles. Moreover, the photocurrent intensity of CNQDs-2/TiO2 was about 25 times higher compared to that of pure TiO2 nanoparticles. Therefore, our research results can provide valuable guidance for exploring high-performance photocatalytic materials. Graphical abstract: The CNQDs/TiO2 composite shows significant improvement in photocatalytic capability. Image 1 Highlights: Carbon nitride quantum dots (CNQDs) were decorated onto the TiO2 nanoparticles. The CNQDs/TiO2 composite shows significant improvement in photocatalytic capability. The heterojunction shows high photocatalytic degradation ability towards bisphenol A. The heterojunction exhibits higher hydrogen evolution rate than that of TiO2 . Bisphenol A degradation mechanism over CNQDs/TiO2 was given.